Beyond SOx reductions from shipping: assessing the impact of NOx and carbonaceous-particle controls on human health and climate. (14th December 2020) - Bilsback, Kelsey R; Kerry, Deanna; Croft, Betty; Ford, Bonne; Jathar, Shantanu H; Carter, Ellison; Martin, Randall V; Pierce, Jeffrey R
Abstract: Historically, cargo ships have been powered by low-grade fossil fuels, which emit particles and particle-precursor vapors that impact human health and climate. We used a global chemical-transport model with online aerosol microphysics (GEOS-Chem-TOMAS) to estimate the aerosol health and climate impacts of four emission-control policies: (1) 85% reduction in sulfur oxide (SOx ) emissions (Sulf); (2) 85% reduction in SOx and black carbon (BC) emissions (Sulf-BC); (3) 85% reduction in SOx, BC, and organic aerosol (OA) emissions (Sulf-BC-OA); and (4) 85% reduction in SOx, BC, OA, and nitrogen oxide (NOx ) emissions (Sulf-BC-OA-NOx ). The SOx reductions reflect the 0.5% fuel-sulfur cap implemented by the International Maritime Organization (IMO) on 1 January 2020. The other reductions represent realistic estimates of future emission-control policies. We estimate that these policies could reduce fine particulate matter (PM2.5 )-attributable mortalities by 13 300 (Sulf) to 38 600 (Sulf-BC-OA-NOx ) mortalities per year. These changes represent 0.3% and 0.8%, respectively, of annual PM2.5 -attributable mortalities from anthropogenic sources. Comparing simulations, we estimate that adding the NOx cap has the greatest health benefit. In contrast to the health benefits, all scenarios lead to a simulated climate warming tendency. The combined aerosol direct radiative effect and cloud-albedo indirect effects (AIE) are between 27 mW m −2 (Sulf) and 41 mW m −2 (Sulf-BC-OA-NOx ). These changes are about 2.1% (Sulf) to 3.2% (Sulf-BC-OA-NOx ) of the total anthropogenic aerosol radiative forcing. The emission control policies examined here yield larger relative changes in the aerosol radiative forcing (2.1%–3.2%) than in health effects (0.3%–0.8%), because most shipping emissions are distant from populated regions. Valuation of the impacts suggests that these emissions reductions could produce much larger marginal health benefits ($129–$374 billion annually) than the marginal climate costs ($12–$17 billion annually).